IMPROVING THE METHODOLOGICAL TRAINING OF FUTURE TEACHERS BASED ON THE INTEGRATION OF THEORY AND PEDAGOGICAL PRACTICE (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the theoretical and methodological foundations for improving the methodological training of future teachers through the integration of theoretical learning and pedagogical practice. It examines the essence and structure of methodological training, its importance in the professional development of teachers, and the discrepancies between students' theoretical knowledge and its practical application. It also explores ways to overcome this gap by creating a holistic, integrated model of teacher training that ensures the unity of theory and pedagogical practice.